Apa Yang Menahan Manusia Durhaka” Dalam 2 Tesalonika 2:6? - Diyestri Ariyani Sekekere; Agustinus Faot; Jonathan Octavianus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
This article addresses various theological debates regarding